KINERJA KEUANGAN PEMERINTAH DESA ARJASA, KECAMATAN ARJASA, KABUPATEN JEMBER TAHUN 2018-2020 - Oryza Ardhiarisca; Novi Ayuni (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
The financial performance of the village government is one way that can be used to obtain an overview of the financial condition of the village. In this study, an analysis will be carried out regarding the financial performance of Arjasa Village in 2018-2022. Performance measurement is carried out using financial ratio analysis. This type of research is descriptive research using secondary data, namely the Village Budget Realization Report in 2018-2020. The results of this study indicate that financial performance based on the compatibility ratio, Arjasa village uses more budget for capital expenditures compared to operating expenditures. Based on the expenditure efficiency ratio, it is known that the Arjasa village government is still less efficient in making budget savings. Based on the effectiveness ratio, it shows that the Arjasa village government has been effective in realizing Village Original Income (PADes). Based on the independence ratio, it shows that the Arjasa Village still relies on funds from transfer revenues or the central government. Based on the growth ratio, it shows that the Arjasa Village experienced fluctuating income growth.